Association between activity limitation and match physical responses of international-level female footballers with cerebral palsy - Berasategui, O.; Castillo, D.; Reina, R.; Henríquez, M.; Iturricastillo, A.; Ascondo, J.; Yanci, J. (European Journal of Human Movement, 2025)
Cerebral palsy (CP) football for female players has a recent development in an international scenario, so this study aimed: (a) to describe performance in activity limitation tests and physical responses in official competition among international-level women`s footballers with CP and according to their sport classes, and (b) to analyze the association between key activity limitation tests used during classification and relevant physical response variables in competition. Thirty-five para-footballers from five national teams that competed in a World competition participated in the study. A cross-sectional and correlational design was used to examine the associations between activity limitation tests and physical responses during competition. Activity limitation was assessed by measuring players' jump capacity, coordination skills, change of direction ability and acceleration capacity. Physical responses were recorded during matches using global positioning system devices. Descriptive data of performance test showed better values in the sport classes with lower impairment. In addition, FT1 players registered the lowest values of physical responses. Significant associations between horizontal jump capacity (Rho = 0.64 to 0.76, p < 0.05), change of direction ability (r/Rho= -0.68 to -0.85, p < 0.05), and acceleration (r = -0.84 to -0.86, p < 0.001) capacity with high-intensity competition variables were found in FT1 players. In addition, a significant association between change of direction ability (Rho = -0.51, p < 0.05) and acceleration capacity (Rho = -0.50, p < 0.05) with the match-specific high-intensity acceleration/deceleration variables was observed in FT2 players. Competition performance in female CP football players that have less activity limitation could be associated with other types of capacities or factors. These results could contribute to optimizing classification protocols and class allocation in female PC football players.